The Role of the Constitutional Court in Impeachment and the Differences in Impeachment Procedures in Indonesia and the United States - Jeane Neltje Saly; Vanessa Wijaya (Jurnal Kewarganegaraan, 2023)
Abstract This research aims to study the impeachment of the president and/or vice president comparatively. The countries compared are countries that adhere to a presidential system, namely Indonesia and the United States. Issues that upbring by this research are how is the role of constitutional court in terms of impeachment and how significant differences in impeachment procedures both in Indonesia and United States. Using normative legal research or library research methods. This research only discusses written regulations, so this research is closely related to libraries because it will require additional data in the library. The results of research, scientific works, statutory regulations, legal theories, and opinions of scholars or doctrine. The power to proselytize the President and/or Vice President is vested in representative bodies, namely the People's Representative Council in the Indonesian Constitutional System and the People's Representative Council in the American Constitutional System. Keywords: Impeachment, President, Vice President; Indonesia; United States.